Deformation-driven metallurgy of graphene nanoplatelets reinforced aluminum composite for the balance between strength and ductility. (15th November 2019) - Xie, Yuming; Meng, Xiangchen; Huang, Yongxian; Li, Junchen; Cao, Jian
Abstract: Despite great strengthening potential of graphene nanoplatelets (GNPs) reinforced aluminum matrix composites, sparked with its high performance with extremely low additions of GNPs, the fatal ductility loss of this composites restricts its applications. The key to obtaining the composites with high comprehensive mechanical performance is the uniformly intragranular dispersion of strengthening phase and the ultrafine microstructures. Here, we present a strategy for GNPs reinforced aluminum composites, namely deformation-driven metallurgy. Multiscale nanostructures were achieved with the structure of nano Al2 O3 dots-GNPs-aluminum matrix, while the vast majority of GNPs were dispersed inside grains uniformly and formed metallurgical bonding with the matrix. Nano-grained microstructure was obtained by the "negative feedback" controlled low heat input and the isolation of the GNPs during dynamic recrystallization. An enhancement of tensile strength by 317% with only 27% ductility loss was achieved, indicating that the deformation-driven metallurgy could provide a novel design strategy for GNPs reinforced aluminum composites. Graphical abstract: Image 1